2002
DOI: 10.1021/bi020012s
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of Hairpin Ribozymes Activated with Short Oligonucleotides

Abstract: We have carried out an in vitro selection to obtain an allosteric hairpin ribozyme, which has cleavage activity in the presence of an exogenous short oligonucleotide as a regulator. Random sequences were inserted in a region corresponding to the hairpin loop of the ribozyme. After 12 rounds of selection, DNA templates were cloned. Of a total of 34 clones, 18 contained the same sequence, and the obtained hairpin ribozymes showed the cleavage activity specifically in the presence of the regulator oligonucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Computer simulations of structure-based modular evolution could complement in vitro evolution experiments in other ways as well. They can be useful in predicting or analyzing the results observed in experiments in which an RNA module is added to a preformed ribozyme or aptamer (Kumar and Joyce 2003;Romero-Ló pez et al 2005), and in optimizing the effect of the combination of modules to develop allosteric ribozymes with relevant biotechnological applications (Komatsu et al 2002;Penchovsky and Breaker 2005). Conversely, the structural invariability of the catalytic domain, which is susceptible to being computationally estimated, could be used as a key criterion in the design of experiments aimed at isolating the core elements of functional RNAs by trimming a longer, in vitro evolved aptamer or ribozyme (Lozupone et al 2003;Wang and Unrau 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations of structure-based modular evolution could complement in vitro evolution experiments in other ways as well. They can be useful in predicting or analyzing the results observed in experiments in which an RNA module is added to a preformed ribozyme or aptamer (Kumar and Joyce 2003;Romero-Ló pez et al 2005), and in optimizing the effect of the combination of modules to develop allosteric ribozymes with relevant biotechnological applications (Komatsu et al 2002;Penchovsky and Breaker 2005). Conversely, the structural invariability of the catalytic domain, which is susceptible to being computationally estimated, could be used as a key criterion in the design of experiments aimed at isolating the core elements of functional RNAs by trimming a longer, in vitro evolved aptamer or ribozyme (Lozupone et al 2003;Wang and Unrau 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been experimentally shown that catalytic RNAs can be enriched with new functional abilities using as a starting point certain domains of pre-existing natural (Jaeger et al 1999) or in vitro evolved (Johnston et al 2001) ribozymes, appended to random-sequence segments. Also, functional motifs have been successfully combined to generate allosteric ribozymes (Tang and Breaker 1997;Komatsu et al 2002), effector-activated ribozymes (Robertson and Ellington 2000), and complex molecules endowed with two activities, such as RNA cleavage and ligation (Landweber and Pokrovskaya 1999;Kumar and Joyce 2003). More recently, a two-step in vitro evolution method was developed that allowed the sequential selection for specific ligand binding and cleavage, so that the evolved catalytic RNAs carried an aptamer domain and a ribozyme one (Romero-Ló pez et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…After overnight incubation with adenine or 3 days of incubation in cleavage buffer alone, the reactions were analyzed by denaturing PAGE and ethidium bromide staining. The observed rate constant values (k obs ) were calculated using the equation S/(S ϩ L) ϭ a(1 Ϫ exp(Ϫk obs t)) (30), where S is the concentration of the cleaved product, L the concentration of the precursor, t is time, and a is the percentage of cleaved product versus total RNA at equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…In prototype approaches, we have used aptamers (Hartig et al 2002), mRNAs , and different microRNAs (Hartig et al 2004) as effector molecules. Other reporter-ribozymes that are regulated by external oligonucleotide effectors have been engineered by exploiting different regulatory mechanisms (Robertson and Ellington 1999;Komatsu et al 2002;Wang et al 2002;Vaish et al 2003;Vauleon and Muller 2003).…”
Section: Introductionmentioning
confidence: 99%